Grandes personajes de la literatura - Nieto, Ramón (Altea, 1975)
Celestina-- Don Quijote-- Don Pablos-- Don Alonso Manrique-- Pedro Crespo-- Don Alvaro-- Don Juan Tenorio-- María-- Mantín Fierro-- Nazarin-- Zalacain-- Joaquín Monegro y Abel Sánchez-- Arturo Cova-- Dña Barbara-- Bernarda Alba-- Cara de Angel